2012
DOI: 10.3892/ol.2012.1071
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cyst fluid analysis for differential diagnosis between benign and malignant lesions

Abstract: The majority of pancreatic cysts are detected incidentally when abdominal imaging is performed during unrelated procedures. The aim of the present study was to assess the diagnostic utility and clinical value of carcinoembryonic antigen (CEA), carbohydrate antigen 19-9 (CA 19-9) and amylase analysis in pancreatic cyst fluid. The study included 52 patients with pancreatic cystic lesions, who underwent fine-needle aspiration biopsy to collect cystic fluid for cytological and biochemical analysis. Cysts were clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 16 publications
4
17
0
Order By: Relevance
“…The cysts were grouped based on the pathological classifications, and they are tested using White’s non parametric t test, two tailed with Benjamini-Hochberg multiple test corrections of P value ( P < 0.05) [ 24 ]. The measured levels of CEA and CA19.9 ranges were used for classification of cysts as cysts, benign cysts, and malignant cysts according to study conducted by Talar-Wojnarowska et al [ 25 ]. Then the classified data was used for the specific bacterial taxa identification between the resected types using the same parameters.…”
Section: Methodsmentioning
confidence: 99%
“…The cysts were grouped based on the pathological classifications, and they are tested using White’s non parametric t test, two tailed with Benjamini-Hochberg multiple test corrections of P value ( P < 0.05) [ 24 ]. The measured levels of CEA and CA19.9 ranges were used for classification of cysts as cysts, benign cysts, and malignant cysts according to study conducted by Talar-Wojnarowska et al [ 25 ]. Then the classified data was used for the specific bacterial taxa identification between the resected types using the same parameters.…”
Section: Methodsmentioning
confidence: 99%
“…However, subsequent small case series have shown that CEA levels may not be accurate as previously reported (sensitivity of 28%-100%, specificity of 25%-100%). [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] AIM The aim of this study was to evaluate the diagnostic performance characteristics of CEA levels in differentiating pancreatic cystic neoplasms (MCNs vs NMCNs) in a large multicenter cohort of consecutive patients undergoing surgical resection of a suspected pancreatic cystic neoplasm.…”
mentioning
confidence: 99%
“…Talar-Wojnarowska et al . [ 4 ] included 52 patients with PCLs and found that CEA was elevated to 238 ± 12.5 ng/mL in patients with malignant cysts. Alkaade et al .…”
Section: Methodsmentioning
confidence: 99%
“…[ 3 ] The pathological types of pancreatic cystic neoplasms (PCNs) include serous cystic neoplasms (SCNs), mucous cystic neoplasms (MCNs), solid false papilloma neoplasms (SPNs), intraductal papillary mucinous neoplasms (IPMNs), and pancreatic neuroendocrine tumors (PNETs). [ 4 ] PPs, SPNs, PNETs, and SCNs are generally regarded as nonmucinous cystic neoplastic lesions and are benign. MCNs and IPMNs are characterized as mucinous cystic neoplastic lesions, and their malignant potential is represented by an adenoma-carcinoma sequence.…”
Section: Introductionmentioning
confidence: 99%